Quality of patient-reported outcome reporting according to the CONSORT statement in randomized controlled trials with glioblastoma patients. Issue 2 (11th November 2020) - Garnier, Louis; Charton, Emilie; Falcoz, Antoine; Paget-Bailly, Sophie; Vernerey, Dewi; Jary, Marine; Ducray, François; Curtit, Elsa
Abstract: Background: Randomized controlled trials (RCTs) represent the best evidence in oncology research. Glioblastoma is the most frequent and deadly primary brain tumor, affecting health-related quality of life. An important end point is patient-reported outcomes (PROs). There are no data regarding how well publications of glioblastoma RCTs report PROs. A specific PRO extension of the Consolidated Standards of Reporting Trials (CONSORT) statement was created to improve the quality of reporting. The aim of this study was to evaluate adherence to the CONSORT-PRO statement in reporting RCTs addressing the treatment of patients with glioblastoma. PRO analysis methodology was explored and criteria associated with higher quality of reporting were investigated. Methods: From PubMed/MEDLINE and the Cochrane Library databases, all phase 2 and 3 RCTs related to glioblastoma published between 1995 and 2018 were reviewed according to the CONSORT-PRO statements. An overall quality score on a 0 to 100 scale was defined based on these criteria and factors associated with this score were identified. Results: Forty-four RCTs were identified as relevant according to predefined criteria. The median overall quality score was 26. No difference was observed regarding reporting quality over the years. CONSORT-PRO items concerning data collection and analysis were poorly reported. Thirty-four trials (77%) used longitudinal data. The most frequent statistical method for PROs analysis was the mean change from baseline (63%). Factors associated with improved overall quality score were the presence of a secondary publication dedicated to PROs results, the statement of any targeted dimensions, and when trials reported results using multiple methods. Conclusion: Despite the importance of measuring PROs in patients with glioblastoma, employment of the CONSORT-PRO statement is poor in RCTs.